Cross-Calibration of GE Healthcare Lunar Prodigy and iDXA Dual-Energy X-Ray Densitometers for Bone Mineral Measurements. (27th April 2016) - Saarelainen, J.; Hakulinen, M.; Rikkonen, T.; Kröger, H.; Tuppurainen, M.; Koivumaa-Honkanen, H.; Honkanen, R.; Hujo, M.; Jurvelin, J. S.
Abstract : In long-term prospective studies, dual-energy X-ray absorptiometry (DXA) devices need to be inevitably changed. It is essential to assess whether systematic differences will exist between measurements with the new and old device. A group of female volunteers (21–72 years) underwent anteroposterior lumbar spine L2–L4 (n = 72 ), proximal femur (n = 72 ), and total body (n = 62 ) measurements with the Prodigy and the iDXA scanners at the same visit. The bone mineral density (BMD) measurements with these two scanners showed a high linear association at all tested sites (r = 0.962 – 0.995 ;p < 0.0001 ). The average iDXA BMD values were 1.5%, 0.5%, and 0.9% higher than those of Prodigy for lumbar spine (L2–L4) (p < 0.0001 ), femoral neck (p = 0.048 ), and total hip (p < 0.0001 ), respectively. Total body BMD values measured with the iDXA were −1.3% lower (p < 0.0001 ) than those measured with the Prodigy. For total body, lumbar spine, and femoral neck, the BMD differences as measured with these two devices were independent of subject height and weight. Linear correction equations were developed to ensure comparability of BMD measurements obtained with both DXA scanners. Importantly, use of equations from previous studies would have increased the discrepancy between these particular DXA scanners, especially at hip and at spine.